Analytical derivation of the effective creep coefficients for timber-concrete composite structures. (1st October 2018) - Schänzlin, J.; Fragiacomo, M.
Abstract: The limitation of the deflection in the long term is often a governing condition when designing timber-concrete composite structures. In order to calculate the long term deflection, the creep deformation is often described by means of creep coefficients. These coefficients are the ratio between the creep and the elastic strain. However in a timber-concrete composite structure the elastic strain is not constant over time, hence an effective creep coefficient has to be introduced and used. This coefficient differs from the pure material creep coefficient provided in the standards. This paper presents an analytical derivation of the effective creep coefficients for a timber-concrete composite structure. Based on the results of an extensive parametric study, a simplified closed-form solution is proposed for the calculation of the effective creep coefficients.